AlN laminate

The laminate structure with a metal component-containing interface allows for efficient laser lift-off of AlN polycrystalline layers, addressing the challenge of mechanical polishing damage and reducing manufacturing time for ultraviolet light emitting devices.

JP7620571B2Active Publication Date: 2025-01-23NGK CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021567341
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-23
Filing Date
2020-12-16
Publication Date
2025-01-23
Estimated Expiration
2040-12-16

AI Technical Summary

Technical Problem

The process of thinning AlN polycrystalline substrates for ultraviolet light emitting devices using mechanical polishing can damage the functional layer, leading to increased manufacturing time and cost due to the need for careful handling.

Method used

A laminate structure comprising an AlN single crystal layer and an AlN polycrystalline layer with a metal component-containing region at the interface, allowing for laser lift-off to easily reduce thickness without affecting the functional layer.

Benefits of technology

The laminate structure enables efficient thinning of the substrate by laser lift-off, reducing manufacturing time and minimizing damage to the functional layer, while maintaining the integrity of the ultraviolet light emitting device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620571000002
    Figure 0007620571000002
  • Figure 0007620571000003
    Figure 0007620571000003
  • Figure 0007620571000004
    Figure 0007620571000004
Patent Text Reader

Abstract

This laminate board is provided with an AlN polycrystalline layer, an AlN single-crystal layer formed on the AlN polycrystalline layer, and a metal component-containing region which contacts the area of interface between the AlN polycrystalline layer and the AlN single-crystal layer and in which multiple metal components are introduced in a dispersed manner.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The technology disclosed in this specification relates to a laminate in which an AlN single crystal layer and an AlN polycrystalline layer are laminated. [Background technology]

[0002] An AlN single crystal plate is sometimes used as a substrate for an ultraviolet light emitting device. For example, Non-Patent Document 1 discloses a method for manufacturing an ultraviolet light emitting device fabricated on an AlN single crystal plate. In Non-Patent Document 1, a functional layer of an ultraviolet light emitting device is formed on an AlN single crystal plate. After the functional layer is formed on the AlN single crystal plate, the AlN single crystal plate is thinned by mechanical polishing in order to improve the ultraviolet light transmittance. [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] Yoshinao Kumagai and 2 others, "HVPE homoepitaxial growth on sublimation AlN wafers and its application to deep UV LEDs", Journal of the Japanese Society for Crystal Growth, Vol. 41, No. 3, 2014, pp. 131-137 Summary of the Invention [Problem to be solved by the invention]

[0004] In the ultraviolet light-emitting device described in Non-Patent Document 1, an AlN single crystal plate is used as a substrate. In the process of forming the functional layer of the ultraviolet light-emitting device, a thick substrate is used to prevent damage to the substrate, but since a thick AlN single crystal plate is expensive, a laminate in which an AlN polycrystalline plate is bonded to an AlN single crystal plate as a support substrate is sometimes used as a handling substrate for producing an ultraviolet light-emitting device. Therefore, after forming a functional layer on the surface of the AlN single crystal plate side of the laminate, the AlN polycrystalline plate is removed by mechanical polishing. However, when the AlN polycrystalline plate is thinned by mechanical polishing, the functional layer may be affected during mechanical polishing. Therefore, in the past, when the AlN polycrystalline plate is thinned by mechanical polishing, it is necessary to perform mechanical polishing carefully to suppress the effect on the functional layer. As a result, the time required to manufacture an ultraviolet light-emitting device increases. Therefore, a laminate that can be easily thinned is required.

[0005] This specification discloses a technique for easily reducing the thickness of a laminate in which an AlN single crystal layer and an AlN polycrystalline layer are laminated. [Means for solving the problem]

[0006] The laminate disclosed in this specification comprises an AlN polycrystalline layer, an AlN single crystal layer formed on the AlN polycrystalline layer, and a metal component-containing region in contact with the interface between the AlN single crystal layer and the AlN polycrystalline layer, into which multiple metal components are introduced in a dispersed manner.

[0007] In the above laminate, a plurality of metal components are dispersed and introduced into the interface between the AlN single crystal layer and the AlN polycrystalline layer. Therefore, for example, by irradiating the laminate with a laser and sublimating (vaporizing) the metal component-containing region, fine cracks are generated in the metal component-containing region, and the laminate can be thinned. That is, the AlN polycrystalline layer of the above laminate can be removed by a method other than mechanical polishing, such as laser lift-off. Therefore, the AlN polycrystalline layer can be easily removed, and the effect on the functional layer of an ultraviolet light-emitting device or the like when removing the AlN polycrystalline layer can be reduced.

Brief Description of the Drawings

[0008] [Figure 1] Schematic diagram of an ultraviolet light-emitting device fabricated using the laminate according to Examples 1 to 3. [Diagram 2] Schematic diagram of the laminate according to Example 1. [Diagram 3] Schematic diagram of the laminate according to Example 2. [Figure 4] Schematic diagram of the laminate according to Example 3.

Embodiments for Carrying Out the Invention

[0009] The main features of the embodiments described below are listed. Note that the technical elements described below are each independent technical elements, which exhibit technical utility alone or in various combinations, and are not limited to the combinations described in the claims at the time of filing.

[0010] The laminate disclosed in this specification is a laminate of an AlN single crystal layer and an AlN polycrystalline layer. Single crystal AlN has, for example, a lattice constant close to or the same as that of a nitride semiconductor such as Al x Ga y N (0 ≦ x ≦ 1, 0 < y ≦ 1). Therefore, the AlN single crystal layer of the laminate disclosed in this specification is useful as a growth substrate for an ultraviolet light-emitting device (UV LED) having a nitride semiconductor as a functional layer. Also, the AlN single crystal plate has, for example, a lattice constant close to or the same as that of a nitride semiconductor such as Al x Ga yThe nitride semiconductor such as N(0≦x≦1,0<y≦1) has a thermal expansion coefficient that is close to or the same as that of the nitride semiconductor. Therefore, it is useful as a handling substrate when manufacturing an ultraviolet light-emitting device. When only an AlN single crystal plate is used as the handling substrate when manufacturing an ultraviolet light-emitting device, it is necessary to use a thick AlN single crystal plate to ensure strength, but the thick AlN single crystal plate is expensive. The laminate disclosed in this specification has an AlN polycrystalline layer provided on the back side of the AlN single crystal layer (the side where the functional layer of the ultraviolet light-emitting device is not provided). The AlN polycrystalline layer can be obtained (or manufactured) at a relatively low cost. Therefore, by laminating the AlN single crystal layer and the AlN polycrystalline layer, a growth substrate with a relatively close lattice constant to the nitride semiconductor and high strength can be realized without using an expensive thick AlN single crystal plate.

[0011] In addition, the laminate disclosed in this specification has a metal component-containing region in which metal components are dispersed and introduced at the interface between the AlN single crystal layer and the AlN polycrystalline layer. Therefore, for example, after an ultraviolet light-emitting device is produced on the AlN single crystal layer of the laminate, the laminate is irradiated with a laser from the AlN polycrystalline layer side, so that the metal components in the metal component-containing region absorb the laser, and the back side (the AlN polycrystalline layer side where the functional layer of the ultraviolet light-emitting device is not provided) from the metal component-containing region can be lifted off. Since the laminate can be thinned in a short time regardless of the thickness of the laminate to be lifted off (removed), the manufacturing time of the ultraviolet light-emitting device can be shortened. That is, even if an ultraviolet light-emitting device is produced using a thick laminate, the time required to manufacture the ultraviolet light-emitting device can be suppressed from increasing. In addition, the thinning of the laminate by laser lift-off can reduce the force (vibration) applied to the functional layer of the ultraviolet light-emitting device compared to thinning by mechanical polishing, and can reduce the influence on the functional layer. The metal component-containing region can be distinguished from the other portions by observing the laminate using an SEM or the like. The laminate disclosed in this specification is not particularly limited, but may have a thickness (distance between the front and back surfaces including the AlN single crystal layer and the AlN polycrystalline layer) of 0.5 to 10.0 mm. The metal component-containing region may be provided in a portion that contacts the interface between the AlN single crystal layer and the AlN polycrystalline layer. That is, the metal component-containing region may be provided in the AlN single crystal layer, may be provided in the AlN polycrystalline layer, or may be provided across both the AlN single crystal layer and the AlN polycrystalline layer.

[0012] In the laminate disclosed in the present specification, the thickness of the metal component-containing region may be, for example, 0.1 μm or more and 5.0 μm or less. That is, the metal component-containing region is provided locally in the thickness direction from the front surface to the back surface of the laminate. If the thickness of the metal component-containing region is 0.1 μm or more, when the laminate is irradiated with a laser, the metal component sufficiently absorbs the laser, the metal component sublimes, fine cracks are generated in the metal component-containing region, and the AlN polycrystalline layer can be lifted off. Also, if the thickness is 5.0 μm or less, it is possible to suppress the cracks generated in the metal component-containing region from extending to parts other than the metal component-containing region (the cracks can be easily contained within the metal component-containing region), and the laminate can be suitably laser lifted off without adversely affecting the ultraviolet light-emitting device. The thickness of the metal component-containing region may be 0.2 μm or more, 0.3 μm or more, 0.5 μm or more, 0.7 μm or more, 1.0 μm or more, or 1.5 μm or more. The thickness of the metal component-containing region may be 4.5 μm or less, 4.0 μm or less, 3.5 μm or less, or 3.0 μm or less.

[0013] In the laminate disclosed in the present specification, the distance between adjacent metal components in the metal component-containing region may be 1 μm or more and 300 μm or less. In other words, the gap between the metal components may be 1 μm or more and 300 μm or less. According to this configuration, if the gap is 1 μm or more, the adverse effect on the ultraviolet light emitting device caused by cracks occurring in the metal component-containing region can be suppressed. Also, if the gap is 300 μm or less, the cracks occurring in the metal component-containing region are connected, and the back side of the AlN single crystal plate can be reliably separated by laser lift-off. Note that "adjacent metal components" refers to metal components adjacent in a direction along (approximately parallel to) the end face in the thickness direction of the AlN polycrystalline layer. The distance between adjacent metal components may be 2 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, or 25 μm or more. Furthermore, the distance between metal components in the metal component-containing region may be 275 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, or 100 μm or less.

[0014] In the laminate disclosed in the present specification, the metal component-containing region may contain at least one metal component selected from Al, Ga, Cu, Fe, Mo, Ni, Ta, and Ti, and may contain at least one of the above metal components as a main component. In addition, "at least one of the metal components as a main component" means that the metal component-containing region contains 50% by weight or more of the above metal components. These elements have high performance in absorbing light in a predetermined range of wavelengths, specifically light of 245 to 1200 nm, and are easily absorbed by laser light. Therefore, with such a configuration, the laminate can be suitably laser lifted off. The metal component in the metal component-containing region may be, for example, a simple metal, an alloy containing the above metal component, or an oxide, a complex oxide, a nitride, a complex nitride, or a complex oxynitride containing the above metal component.

[0015] In the laminate disclosed in the present specification, the metal component-containing region may contain at least one metal component selected from Al, Ga, Cu, and Ni. The above-mentioned metal component materials are relatively easy to obtain, and are particularly easy to absorb laser light, so that they can be suitably laser lifted off.

[0016] In the laminate disclosed in the present specification, the metal component may be in the form of particles. In this case, the metal component (particles containing a metal component) may have an aspect ratio greater than 1 and less than or equal to 10. In this case, the metal component may be present in the metal component-containing region such that the long side is along (approximately parallel to) the first surface (or the first surface and the second surface). Specifically, the long side of the metal component may be arranged to form an angle of less than 20 degrees with respect to the first surface. If the aspect ratio of the metal component is greater than 1, the area of ​​the surface along the first surface is sufficiently large, the laser absorption efficiency is improved, and laser lift-off can be performed efficiently, and cracks occurring in the metal component-containing region tend to occur along approximately parallel to the first surface (or the first surface and the second surface), thereby suppressing adverse effects on the ultraviolet light-emitting device. In addition, if the aspect ratio is less than or equal to 10, the metal component can be easily introduced into the AlN single crystal plate. The aspect ratio may be 0.5 or more, 1.0 or more, 1.5 or more, or 2.0 or more. The aspect ratio may be 8 or less, 7 or less, 5 or less, or 3 or less.

[0017] Furthermore, when a material containing the above-mentioned metal component is introduced into the metal component-containing region, the Young's modulus of the metal component-containing region becomes smaller than that of the AlN single crystal layer and the AlN polycrystalline layer. Therefore, when the metal component-containing region is provided at the interface between the AlN single crystal layer and the AlN polycrystalline layer, the distortion caused by the difference in thermal expansion coefficient between the AlN single crystal layer and the AlN polycrystalline layer can be alleviated. Therefore, during heat treatment, etc., the force applied from the AlN polycrystalline layer to the AlN single crystal layer based on the difference in thermal expansion coefficient between the AlN single crystal layer and the AlN polycrystalline layer can be reduced. As a result, the occurrence of warping or cracks in the AlN single crystal layer can be reduced. EXAMPLES

[0018] Example 1 Hereinafter, a description will be given of the laminated plate 10 according to the embodiment. The laminated plate 10 is used as a handling substrate for producing the ultraviolet light-emitting device 1. Therefore, before describing the laminated plate 10 in detail, a brief description will be given of the ultraviolet light-emitting device 1 that uses the laminated plate 10 as a handling substrate.

[0019] The ultraviolet light emitting device 1 is an ultraviolet light emitting diode (UV LED), and includes an AlN single crystal layer 12, an n-type nitride semiconductor layer 2, a p-type nitride semiconductor layer 3, and a light emitting layer 4. The n-type nitride semiconductor layer 2 is provided on the surface of the AlN single crystal layer 12. The light emitting layer 4 is provided on a part of the surface of the n-type nitride semiconductor layer 2 (the right side in FIG. 1). Therefore, the light emitting layer 4 is provided on a part of the surface of the n-type nitride semiconductor layer 2, and the other part is exposed. The p-type nitride semiconductor layer 3 is provided on the surface of the light emitting layer 4. That is, the light emitting layer 4 is provided between the n-type nitride semiconductor layer 2 and the p-type nitride semiconductor layer 3. Electrodes (not shown) are provided on the surface of the p-type nitride semiconductor layer 3 and on the exposed part of the surface of the n-type nitride semiconductor layer 2. Although not shown in the drawings, in practice, the n-type nitride semiconductor layer 2 may be formed of a plurality of layers, the p-type nitride semiconductor layer 3 may be formed of a plurality of layers, and the light emitting layer 4 may be formed of a plurality of layers. The materials and the number of layers of the n-type nitride semiconductor layer 2, the p-type nitride semiconductor layer 3, and the light emitting layer 4 can be appropriately selected depending on the application of the ultraviolet light emitting device 1.

[0020] When the ultraviolet light emitting device 1 is manufactured, first, the n-type nitride semiconductor layer 2 is formed on the surface of the laminated plate 10 of this embodiment (specifically, on the surface of the AlN single crystal layer 12). Next, the light emitting layer 4 is formed on the surface of the formed n-type nitride semiconductor layer 2, and the p-type nitride semiconductor layer 3 is formed on the surface of the formed light emitting layer 4. After that, the light emitting layer 4 and the p-type nitride semiconductor layer 3 are partially removed to expose a part of the surface of the n-type nitride semiconductor layer 2. In order to form the nitride semiconductor layers 2, 3, and 4 of good quality, the nitride semiconductor layers 2, 3, and 4 are formed on the surface of the laminated plate 10 (the surface of the AlN single crystal layer 12). In order to facilitate the formation and processing of the n-type nitride semiconductor layer 2, the p-type nitride semiconductor layer 3, and the light emitting layer 4, a thick laminated plate 10 is used as a handling substrate when the ultraviolet light emitting device 1 is manufactured. On the other hand, since the laminate 10 has the AlN single crystal layer 12 and the AlN polycrystalline layer 14 laminated thereon, if the laminate 10 is used as it is as a substrate for the ultraviolet light-emitting device 1, the AlN polycrystalline layer 14 makes it difficult for the emitted light (ultraviolet light) to pass through the laminate 10. Therefore, after the n-type nitride semiconductor layer 2, the p-type nitride semiconductor layer 3, and the light-emitting layer 4 are formed, the laminate 10 is thinned to a required thickness. That is, the AlN polycrystalline layer 14, which is an unnecessary portion of the laminate 10, is removed so that only the AlN single crystal layer 12 required as a substrate remains. Hereinafter, the n-type nitride semiconductor layer 2, the p-type nitride semiconductor layer 3, and the light-emitting layer 4 may be collectively referred to as "functional layers".

[0021] As shown in FIG. 2, the laminate 10 includes an AlN single crystal layer 12 and an AlN polycrystalline layer 14. The AlN single crystal layer 12 is made of single crystal AlN. The AlN polycrystalline layer 14 is made of polycrystalline AlN. In this embodiment, for example, single crystal AlN and polycrystalline AlN are defined as follows. Using an XRD device (D8-DISCOVER manufactured by Bruker-AXS), an XRC profile of the (002) plane of the AlN single crystal layer is measured using CuKα radiation under the conditions of a voltage of 40 kV, a current of 40 mA, a collimator diameter of 0.5 mm, an anti-scattering slit of 3 mm, and an ω step width of 0.01° for a counting time of 1 second. Then, a measurement is performed using the half-width based on the obtained XRC profile, and a measurement value of less than 10,000 arcsec is referred to as single crystal AlN, and a measurement value of 10,000 arcsec or more is referred to as polycrystalline AlN. Both the AlN single crystal layer 12 and the AlN polycrystalline layer 14 can be formed by, for example, sublimation. The method of forming the AlN single crystal layer 12 and the AlN polycrystalline layer 14 is not particularly limited, and the AlN single crystal layer 12 and the AlN polycrystalline layer 14 can also be formed by other methods, such as vapor phase film formation methods such as CVD, HVPE, MBE, and sputtering, liquid phase film formation methods such as hydrothermal and Na flux methods, and room temperature bonding in which single crystal AlN and polycrystalline AlN are bonded by a surface activation method.

[0022] The laminate 10 also includes a metal component-containing region 16 provided between the front surface 20 and the back surface 22. Specifically, the metal component-containing region 16 is disposed in an interface portion (hereinafter also simply referred to as an "interface portion") between the AlN single crystal layer 12 and the AlN polycrystalline layer 14, and in this embodiment, the metal component-containing region 16 is disposed across both the AlN single crystal layer 12 and the AlN polycrystalline layer 14 in the interface portion. In this embodiment, when the ultraviolet light-emitting device 1 is manufactured using the laminate 10 as a handling substrate, the surface of the laminate 10 on which the functional layer is formed (i.e., the exposed surface of the AlN single crystal layer 12 in the thickness direction) is referred to as the front surface 20, and the opposite surface (i.e., the exposed surface of the AlN polycrystalline layer 14 in the thickness direction) is referred to as the back surface 22. The metal component-containing region 16 is provided locally in the thickness direction of the laminate 10 and is provided approximately parallel to the back surface 14.

[0023] The metal component-containing region 16 is disposed across both the AlN single crystal layer 12 and the AlN polycrystalline layer 14 at the interface between the AlN single crystal layer 12 and the AlN polycrystalline layer 14. In the metal component-containing region 16, a plurality of metal particles are dispersed and introduced into the AlN single crystal layer 12 and the AlN polycrystalline layer 14. Specifically, the metal particles in the metal component-containing region 16 have an aspect ratio adjusted to be greater than 1 and less than or equal to 10, and are disposed so that their long sides are aligned along the front surface 12 and the back surface 14. In addition, each metal particle is disposed at intervals such that the distance between adjacent metal components is 1 μm to 300 μm. The method of introducing the metal particles (metal components) is not particularly limited. For example, the metal component-containing region 16 can be formed by mixing a raw material containing a metal component into the raw material (solid raw material or raw material gas) that forms the AlN single crystal layer 12. Alternatively, the metal component-containing region 16 can be formed by attaching a raw material containing a metal component to the surface of the AlN polycrystalline layer 14, forming the AlN single crystal layer 12 on the surface of the AlN polycrystalline layer 14, and diffusing the metal component near the interface between the AlN single crystal layer 12 and the AlN polycrystalline layer 14. The metal particles are simple metals selected from Al, Ga, Cu, Fe, Mo, Ni, Ta, and Ti. The metal component-containing region 16 contains at least one of the above metal components as a main component. The metal particles may be an alloy containing the above metal element, an oxide or composite oxide containing the above metal element, a nitride or composite nitride containing the above metal component, or a composite oxynitride containing the above metal component.

[0024] The impurity metal component-containing region 16, which contains the metal component, prevents the laser light from passing from the front surface 20 to the back surface 22 of the laminate 10 (or from the back surface 22 to the front surface 20). Specifically, when the back surface 22 of the laminate 10 is irradiated with ultraviolet laser light, the metal particles in the metal component-containing region 16 absorb the ultraviolet laser light. As a result, the metal component in the metal component-containing region 16 sublimes (vaporizes), causing fine cracks in the metal component-containing region 16, and the AlN polycrystalline layer 14 can be removed (lifted off). The metal particles introduced into the metal component-containing region 16 are selected to easily absorb laser light. Specifically, metal particles that easily absorb light with a wavelength of 245 nm to 1200 nm are introduced into the metal component-containing region 16.

[0025] Table 1 below shows an example of metals that easily absorb light with wavelengths of 245 nm to 1200 nm. The metals shown in Table 1 (Al, Ga, Cu, Fe, Mo, Ni, Ta, Ti) suitably absorb laser light with wavelengths of 245 nm to 1200 nm. Table 1 also shows the absorbance of the above metals for light with wavelengths of 400 nm and 800 nm. The metals shown in Table 1 (Al, Ga, Cr, Cu, Fe, Mo, Ni, Ta, Ti) absorb light with wavelengths of 245 nm to 1200 nm well. Therefore, when irradiated with laser light with wavelengths of 245 nm to 1200 nm, metal particles containing these elements absorb the laser light and vaporize. Since the metal component-containing region 16 is provided approximately parallel to the back surface 22 of the laminate 10, the laminate 10 is divided at the portion where the metal particles containing the above elements are introduced (i.e., the interface portion). Therefore, the laminate 10 in which metal particles containing at least one of the above elements have been introduced into the interface portion is thinned at the metal component-containing region 16 (i.e., the interface portion) by laser lift-off. This allows the AlN polycrystalline layer 14 to be separated from the laminate 10. Furthermore, since the metal component-containing region 16 is disposed in both the AlN single crystal layer 12 and the AlN polycrystalline layer 14 at the interface portion, the laminate 10 separates substantially the entire AlN polycrystalline layer 14. This allows the time for mechanical polishing after laser lift-off to be shortened.

[0026] [Table 1]

[0027] Furthermore, when the above elements are introduced into the metal component-containing region 16, the metal component-containing region 16 can relax the distortion caused by the difference in thermal expansion coefficient between the AlN single crystal layer 12 and the AlN polycrystalline layer 14 at the interface. The single crystal AlN constituting the AlN single crystal layer 12 and the polycrystalline AlN constituting the AlN polycrystalline layer 14 have relatively close thermal expansion coefficients, but they are slightly different. Therefore, in the heat treatment process when manufacturing the ultraviolet light-emitting device 1, a difference occurs in the amount of deformation (amount of elongation) between the AlN single crystal layer 12 (the portion where the metal component-containing region 16 is not provided) and the AlN polycrystalline layer 14 (the portion where the metal component-containing region 16 is not provided). If the metal component-containing region 16 is not provided, distortion occurs at the interface between the AlN single crystal layer 12 and the AlN polycrystalline layer 14, and deterioration such as warping and cracking may occur in the AlN single crystal layer 12. The laminate 10 of this embodiment has the metal component-containing region 16 at the interface. The Young's modulus of the metal component-containing region 16 is smaller than the Young's modulus of the AlN single crystal layer 12 and the AlN polycrystalline layer 14. Therefore, the metal component-containing region 16 can relieve distortion caused by the difference in thermal expansion coefficient between the AlN single crystal layer 12 and the AlN polycrystalline layer 14 at the interface. Since deterioration of the AlN single crystal layer 12 can be suppressed and the ultraviolet light-emitting device 1 can be formed on the surface of the good quality AlN single crystal layer 12, adverse effects on the functional layer of the ultraviolet light-emitting device 1 can be reduced.

[0028] In this embodiment, for example, the thickness L1 of the laminate 10 is adjusted to 0.5 mm to 10.0 mm, and the thickness L2 of the metal component-containing region 16 is adjusted to 0.1 μm to 5.0 μm. The thickness L1 of the laminate 10 is the length between the front surface 20 and the back surface 22, and indicates the length in the direction perpendicular to the front surface 20 and the back surface 22. In other words, the thickness L1 of the laminate 10 is the length from the exposed surface of the AlN single crystal layer 12 to the exposed surface of the AlN polycrystalline layer 14 via the interface portion. The thickness L2 of the metal component-containing region 16 also indicates the length in the direction perpendicular to the front surface 20 and the back surface 22. By setting the thickness L2 of the metal component-containing region 16 to 0.1 μm or more, the metal particles (metal components) can reliably absorb the laser light (the laser light does not pass through the metal component-containing region 16), and the effect of generating fine cracks in the metal component-containing region 16 can be obtained. That is, laser lift-off can be performed in the metal component-containing region 16. Furthermore, by making the thickness L2 0.1 μm or more, it is possible to more reliably obtain the effect of reducing defects (deterioration of the AlN single crystal layer 12) caused by the difference in thermal expansion coefficient between the AlN single crystal layer 12 and the AlN polycrystalline layer 14. Furthermore, by making the thickness L2 5.0 μm or less, it is possible to confine the generation of cracks due to the irradiation of the laser light within the metal component-containing region 16. Therefore, it is possible to suppress adverse effects on the ultraviolet light emitting device.

[0029] Example 2 In the above-mentioned Example 1, the metal component-containing region 16 is disposed in both the AlN single crystal layer 12 and the AlN polycrystalline layer 14, but is not limited to such a configuration. The metal component-containing region may be disposed at the interface between the AlN single crystal layer 12 and the AlN polycrystalline layer 14, and for example, as shown in FIG. 3, the impurity region 116 may be disposed in the AlN single crystal layer 12. In this example, the metal component-containing region 116 is different from the metal component-containing region 16 in Example 1, and the other configurations are substantially the same. Therefore, a description of the same configuration as the laminate 10 in Example 1 will be omitted.

[0030] 3, the metal component-containing region 116 of the laminate 110 is disposed in the AlN single crystal layer 12. That is, the metal component is introduced into the AlN single crystal layer 12 at the interface between the AlN single crystal layer 12 and the AlN polycrystalline layer 14. Note that the type of metal component introduced into the metal component-containing region 116 and the thickness L2 of the metal component-containing region 116 are the same as those of the metal component-containing region 16 in Example 1, and therefore detailed description thereof will be omitted.

[0031] In this embodiment as well, the laminate 110 is separated at the metal component-containing region 116 by laser lift-off. That is, since the metal component-containing region 116 is disposed in the AlN single crystal layer 12 at the interface portion, the laminate 110 has the AlN polycrystalline layer 14 entirely separated by laser lift-off. Therefore, the AlN polycrystalline layer 14 can be suitably separated from the laminate 10 by laser lift-off. In addition, the metal component-containing region 116 reduces defects (deterioration of the AlN single crystal layer 12) caused by the difference in thermal expansion coefficient between the AlN single crystal layer 12 and the AlN polycrystalline layer 14.

[0032] Example 3 Furthermore, the metal component-containing region only needs to be located at the interface between the AlN single crystal layer 12 and the AlN polycrystalline layer 14, and for example, as shown in Fig. 4, the metal component-containing region 216 may be located within the AlN polycrystalline layer 14. In this embodiment, the metal component-containing region 216 differs from the metal component-containing region 16 in Example 1, and the other configurations are substantially the same. Therefore, a description of the same configuration as the laminate 10 in Example 1 will be omitted.

[0033] 4, the metal component-containing region 216 of the laminate 210 is disposed in the AlN polycrystalline layer 14. That is, the metal component is introduced into the AlN polycrystalline layer 14 at the interface between the AlN single crystal layer 12 and the AlN polycrystalline layer 14. Note that the type of metal component introduced into the metal component-containing region 216 and the thickness L2 of the metal component-containing region 116 are the same as those of the metal component-containing region 16 in Example 1, and therefore detailed explanations will be omitted.

[0034] In this embodiment as well, the metal component-containing region 216 can reduce defects caused by the difference in thermal expansion coefficient between the AlN single crystal layer 12 and the AlN polycrystalline layer 14. Furthermore, the laminate 210 is separated at the metal component-containing region 216 by laser lift-off. That is, even if the metal component-containing region 216 is provided in the AlN polycrystalline layer 14, the metal component-containing region 216 is disposed in contact with the interface between the AlN single crystal layer 12 and the AlN polycrystalline layer 14, so that the laminate 110 is separated at the interface by laser lift-off. Therefore, since the AlN polycrystalline layer 14 is almost completely removed by laser lift-off, the mechanical polishing time can be significantly reduced compared to the conventional method of thinning the laminate by mechanical polishing alone.

[0035] Although specific examples of the technology disclosed in this specification have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes to the specific examples exemplified above. Furthermore, the technical elements described in this specification or drawings exhibit technical usefulness alone or in various combinations, and are not limited to the combinations described in the claims at the time of filing.

Claims

1. an AlN polycrystalline layer; an AlN single crystal layer formed on the AlN polycrystalline layer; a metal component-containing region in contact with an interface between the AlN single crystal layer and the AlN polycrystalline layer, into which a plurality of metal components are introduced in a dispersed manner; The metal component is a laminate having Ga as a main component.

2. The laminate according to claim 1 , wherein the thickness of the metal component-containing region is 0.1 μm or more and 5.0 μm or less.

3. 3. The laminate according to claim 1, wherein the distance between adjacent metal components in the metal component-containing region is 1 μm or more and 300 μm or less.

4. The laminate according to any one of claims 1 to 3, wherein the metal component has an aspect ratio greater than 1 and less than or equal to 10, and the long side is present along the thickness direction end face of the AlN polycrystalline layer.

Citation Information

Patent Citations

  • Method for realizing a self-supporting substrate of group III nitrides by heteroepitaxy on a sacrificial layer

    JP2007506635A

  • Manufacturing method of nonpolar plane group iii nitride single crystal

    JP2009018975A

  • Method for producing laminate having aluminum nitride single crystal layer, laminate produced by the method, method for producing aluminum nitride single crystal substrate using the laminate, and aluminum nitride single crystal substrate

    JP2011020900A

  • JP2014、41

  • Method for manufacturing group iii nitride film and method for manufacturing group iii nitride semiconductor device

    JP2015040136A